Women of Andalusian Court: Kingmakers, Advisors and Regents - Noor Syuhada Binti Shahidan; Nurul Shahirah Binti Majlan (IIUM Journal of Religion and Civilisational Studies, 2024)
This research paper explores the often overlooked yet significant political roles played by women in the Islamic Civilization of al-Andalus. Despite the predominance of men in administrative positions, women from the Andalusian court exercised authority as kingmakers, advisors, and, in rare cases, regents. It began by establishing the historical context of al-Andalus and the presence of women in politics whilst emphasizing the societal loss resulting from their exclusion in the three main roles examined. Furthermore, the paper addresses how these women wielded political influence, their strategies, and the cultural contexts that shaped their roles. The paper would also briefly explore the challenges and lack of societal recognition faced by the women. Despite limited translated sources, it highlights the importance of studying the political contributions of Andalusian court women for a deeper understanding of Islamic history in Spain.